Treatment for chemotherapy-induced peripheral neuropathy: A systematic review of randomized control trials - Wang, Chenkun; Chen, Si; Jiang, Weiwei (Frontiers in Pharmacology, 2022)
Purpose: The treatment of CIPN (chemotherapy induced peripheral neuropathy) is a thorny issue for clinicians and many clinical trials and meta analysis also are controversial. There are also few comparisons of efficacy between drugs that treat CIPN. Therefore, this review aimed to study the efficacy of drugs for the CIPN treatment in existing randomized controlled trials. Methods: Electronic databases were searched for randomized controlled trials (RCTs) comparing any pharmaceutical intervention and/or combination about treating CIPN. Results: We included 17 RCTs investigating 16 medicine categories of CIPN treatment : Duloxetine, pregabalin, crocin, tetrodotoxin, venlafaxine, monosialotetrahexosylganglioside (GM1), lamotrigine, KA (ketamine + amitriptyline), cream, lamotrigine, nortriptyline, amitriptyline, topical Citrullus colocynthis (bitter apple) oil, BAK (baclofen, amitriptyline hydrochloride and ketamine) pluronic lecithin organogel, gabapentin, and acetyl l-carnitine (ALC). Small sample sizes, and short follow-up periods are the features of most of the included RCTs. It is difficult to quantify because of the highly variable outcome indicators. Conclusion: Duloxetine, venlafaxine, pregabalin, crocin, tetrodotoxin, and monosialotetrahexosylganglioside were demonstrated some benefits for treating CIPN. Duloxetine, GM1, Crocin are considered of moderate benefit based on the evidence review. Lamotrigine, KA cream, nortriptyline, amitriptyline, topical Citrullus colocynthis (bitter apple) oil are not considered to be beneficial for CIPN treatment. Further studies were also required to confirm the efficacy of gabapentin in the treatment of CIPN because of a controversy of efficacy of gabapentin. Furthermore, BAK topical compound analgesic gel only had a tendency to improve CIPN symptoms, which was not statistically significant. ALC may result in worse CIPN. And most studies were lacking in quality because of low sample sizes. Thus, large sample, high-quality, standardized randomized controlled trial were needed to critically assess the effectiveness for CIPN treatment in future.